PENERAPAN EDUTAINMENT DALAM PENDIDIKAN ANAK USIA DINI (PAUD) MELALUI MODEL PEMBELAJARAN BCCT (BEYOND CENTER AND CIRCLE TIME) / SENTRA - Hastuti, Dwi (Widya Wacana: Jurnal Ilmiah, 2015)
Curriculum structure of Early Childhood Education contains development programswhich cover religion and moral values, physical ability, cognitive, language, social emotionaland arts. These aspects need improvement through learning in Early Childhood Education.Child`s world is world of play. The most effective way a child to learn is through games becausechildren will never bored, they will happy when they played, and with playing the children canlearn a lot about things.Today learning in Early Childhood Education have a lot of distortion. There are a lot ofEarly Childhood Education institution applying learning with teacher centered style, this can beobserve by the children just only sit, hear, and must do their homework without option to chooselearning activity which held. For various Early Childhood Education aspects can developoptimally, needs an innovative learning approach which fun in Early Childhood Education. Oneof the approach is edutainment concept through BCCT.Keywords: Early Childhood Education, Edutainment, BCCT (Beyond Center and Circle Time)